Discount venture brands: Self-congruity and perceived value-for-money? - Baker, Thomas L.; Chari, Simos; Daryanto, Ahmad; Dzenkovska, Julija; Ifie, Kemefasu; Lukas, Bryan A.; Walsh, Gianfranco (Journal of business research, 2020)
Grocery retailers have begun to target price conscious consumers with a new type of budget brand, called discount venture brands. These brands are exclusive to the retailer. Sharing the same price point as economy private-label brands, the aim of discount venture brands is to attract customers with an overall look-and-feel that is not explicitly premium, yet is more attractive than that of conventional budget brands. Drawing on the self-congruity literature, the authors explore two questions: (1) whether customers perceive discount venture brands to offer greater value-for-money than conventional budget brands; and (2) whether such perceptions translate to customer impressions about the retailer brand? Results from a scenario-based experiment involving 505 participants suggest that, in comparison with conventional budget brands, discount venture brands may be less conducive to engendering favorable value-for-money perceptions; in short, discount venture brands may be less effective than conventional budget brands. This finding can be explained with a concept called self-congruity. Overall, we show that self-congruity acts as an indirect-only mediator of the path between the type of a brand and value-for-money perceptions of the brand. Particular findings are that self-congruity has a positive effect on value-for-money perceptions associated with conventional budget brands, discount venture brands, and the retailers selling those brands. However, for consumers with a preference for brands with a budget price point, self-congruity appears to be higher for conventional budget brands than discount venture brands; and this difference in self-congruity is more pronounced when shopping for others than when shopping for oneself.